Rural pig production systems and breeding preferences of pig farmers in northern Ghana - Ayizanga, R.A.; Kayang, B.B.; Adomako, K.; Asamoah, L. (2018)
A questionnaire was administered to 74 purposively selected respondents in order to describe the farming system under which pigs are kept in eight randomly selected communities from the IITA/ Africa RISING intervention communities in the three regions of northern Ghana and to document their peculiar farming systems and constraints with an aim of helping the farmers find sustainable solutions to these challenges. The study also sought to help farmers identify and prioritise breeding objectives using a participatory approach. Generally, two to three pigs were kept as part of a mixed subsistence farming system with little scientific knowledge on pig husbandry since a vast majority of them are not literate and have never received any training on pig husbandry. The constraints faced by most of the pig farmers included diseases, inadequate feed and poor housing facilities. Besides, the farmers have no set breeding objectives as mating is mostly uncontrolled and haphazardly done. It will be useful if the farmers are educated and encouraged to form interest groups to enable them elicit assistance from both governmental and non-governmental organisations to help address some of their production challenges, access better markets and to enhance their bargaining power.